2020
DOI: 10.1111/jocs.14430
|View full text |Cite
|
Sign up to set email alerts
|

Heart transplantation and in‐hospital outcomes in adult congenital heart disease patients with Fontan: A decade nationwide analysis from 2004 to 2014

Abstract: Introduction Treatment of adult congenital heart disease patients who require advanced therapies remains challenging due to high perioperative and wait‐list mortality and limited donors. Patients palliated with Fontan are at the highest risk of early mortality due to multiorgan involvement and few centers able to safely transplant them. We sought to evaluate the early outcomes of heart transplants in these adult Fontan patients. Methods Using the Nationwide Inpatient Sample database, we identified all adults a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 24 publications
(40 reference statements)
2
26
1
Order By: Relevance
“…In general, transfusion of blood and blood products is associated with an increased incidence of renal failure, infection, as well as respiratory, cardiac, and neurologic complications after cardiac surgery 10,19 . Although our study did not demonstrate significant differences in outcomes, previous studies have shown that OHT outcomes are worse for patients with SV physiology, compared to BV physiology 2,20 . Early referral before liver dysfunction is likely to reduce perioperative complications, especially in SV physiology patients 2 …”
Section: Resultscontrasting
confidence: 54%
See 3 more Smart Citations
“…In general, transfusion of blood and blood products is associated with an increased incidence of renal failure, infection, as well as respiratory, cardiac, and neurologic complications after cardiac surgery 10,19 . Although our study did not demonstrate significant differences in outcomes, previous studies have shown that OHT outcomes are worse for patients with SV physiology, compared to BV physiology 2,20 . Early referral before liver dysfunction is likely to reduce perioperative complications, especially in SV physiology patients 2 …”
Section: Resultscontrasting
confidence: 54%
“…10,19 Although our study did not demonstrate significant differences in outcomes, previous studies have shown that OHT outcomes are worse for patients with SV physiology, compared to BV physiology. 2,20 Early referral before liver dysfunction is likely to reduce perioperative complications, especially in SV physiology patients. 2 Liver congestion/cirrhosis is common in our SV cohort.…”
Section: Commentsmentioning
confidence: 99%
See 2 more Smart Citations
“…After the initial 30 days patients with ACHD have a superior longterm survival compared with non-CHD adults [116]. In the Fontan population mortality remains high [117]. Identifying the appropriate time for successful heart transplant is one of the most difficult aspects of caring for adults with CHD.…”
Section: Advanced Therapymentioning
confidence: 99%